ALAT PENDETEKSI KECEPATAN KENDARAAN BERMOTOR MENGGUNAKAN MIKROKONTOLLER DAN WEBCAM BERBASIS PERSONAL COMPUTER - Setianingrum, Ira (Jurnal Informatika, 2011)
Development of technology at automotive engineering will be impact the fastest of motor cycle. To protecting the traffic accident on the road needed a regulation about maximum and minimum limitation speed of motor cycle. This article offer an alternative tools to reduce traffic accident with detection tools using webcam and microcontroller based on personal computer. Methodology used is design of block system diagram, hardware and software design, testing and later is report analysis. The final result is a tools to detection the speed of motor cycle that exceed the limitation of maximum speed, censor will send a signal to computer, then webcam will automatically capture the image, so it can be identification the rider who break the law. Keywords: Motorcycle, Detection, PC